Relationship between reproductive exposures and age-related cataract in women - Noran, N.H.; Salleh, N.; Zahari, M. (SAGE Publications, 2007)
The objective of this study is to evaluate the relationship between reproductive exposures and age-related cataract among women. This was a hospital based case-control study. The study population included female patients, aged 50 years and above who attended the Eye clinic at the University of Malaya Medical Centre. The outcome measurement was based on ophthalmologic examination by an ophthalmologist. The data on exposure was obtained from face to face interview using a structured questionnaire. In order to reduce the recall bias, patients' medical records were used to substantiate the exposure status. Multiple logistic regression was used to assess the association of age-related cataract with exogenous estrogen usage (HRT and OCP) and duration of menses. Important confounders such as age, history of diabetes, cigarette smoking and steroids usage were controlled for in the analysis. Females with 29 years or less of endogenous estrogen exposure of, have almost three times the risk of developing age related cataract (adjusted OR 3.42: 95% CI: 1.28,9.16), similarly among those with exposure of 30- 32 years (adjusted OR 3.64: 95% CI: 1.08,12.26). Hormone Replacement Therapy used for more than three years was found to be a protective factor of age-related cataract. There is evidence that reproductive exposure may play a role in reducing the occurrence of age-related cataract among Malaysian women.